Metabolic syndrome does not impair the response to alfuzosin treatment in men with lower urinary tract symptoms: a double-blind, randomized, placebo-controlled study - Altin, Selcuk; Ozan, Tunc; Ilhan, Selcuk; Ilhan, Nevin; Onur, Rahmi (Aves, 2015)
Objective: This study is a placebo-controlled comparison of the response to alfuzosin treatment for lower urinary tract symptoms (LUTS) in patients with and without metabolic syndrome (MetS). Material and methods: A total of 80 men with LUTS were included in the study. Patients had a maximum flow rate of <15 mL/sec, prostate volume of >20 mL, and International Prostate Symptom Score (IPSS) of >8. All eligible men (n=68) for evaluation were initially divided into two groups as MetS (n=34) and non-MetS (n=34) groups. Patients were further randomized to receive alfuzosin (10 mg/day) or placebo (n=17/group; a total of four groups). The outcome was measured at 12th week according to the changes from baseline in IPSS, quality of life (QoL) scores, maximum flow rate (Qmax), and postmictional residue. Results: Alfuzosin significantly improved LUTS in men with and without MetS compared with patients receiving placebo (p<0.05). Mean IPSS scores in treatment groups decreased significantly, whereas patients receiving placebo had no statistically significant difference (p>0.05). Similarly, alfuzosin treatment resulted in a significant increase in Qmax in patients with LUTS/benign prostatic enlargement when compared with patients in placebo group (p<0.05). Mean QoL scores measured by IPSS-QoL and QoL questionnaires also improved significantly in patients receiving alfuzosin for 3 months regardless of the presence of MetS (p<0.05). Conclusion: Our results revealed that the presence of MetS in patients with LUTS did not impair the response to alfuzosin treatment.
Keywords: Alfuzosin; lower urinary tract symptoms treatment; metabolic syndrome